The Effect of Fatigue on Soccer Players’ Coordination Abilities - Jamal Abubshara (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Coaches must translate what has occurred in the match into training activities which are linked to these guidelines. This must be done in such a way that they can be executed again in the matches, most coaches do not reach the final step, they do not reach further than creating general training exercises, which hardly have any relation to problems that occurred in the match, fatigue is one of the main problems which effect on performance skills and other variables, nonetheless, co-ordination abilities during matches and high intensity exercise are still controversial. Aim: The aim of this study was to examine the effect of acutely induced fatigue on soccer players ‘coordination skills Methods: , The researcher used quasi-experimental method and conducted the study on a purposive sample (S) of (11) eleven experienced elite male soccer players performed three co-ordination abilities tests (dribbling 30 seconds, weight passing correctly to specified distance 15,25,35 m, and short dribbling test) prior to and after the implementation of an intensive and intermittent exercise protocol. In order to process the data T-test was used, the results revealed significant difference between pre-test and post-test values of co-ordination abilities test scores (p<0.01). Heart rate before the shooting test was HR (89.28 ±4.03) bmp, and heart rate after fatigue was measured at (174.39±12.24) bmp. Results: The results confirmed the study hypothesis regarding the negative influence of fatigue on co-ordination abilities (rhythm, differentiation, orientation). Conclusion: It is concluded that coaches should train the players under exertion condition to decrease the effects of fatigue on co-ordination abilities level.